2008
DOI: 10.1002/ejsp.566
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive load, trigger salience, and the facilitation of triggered displaced aggression

Abstract: Researchers hypothesize that a state of limited cognitive processing capacity increases aggression. In the context of the triggered displaced aggression (TDA) paradigm, a 2 (Salience of triggering event: high/low) Â 2 (Cognitive load at trigger: yes/no) Â 2 (Cognitive load at aggression: yes/no) between participants experiment tested this hypothesis. Results showed that inducing cognitive load in previously provoked participants while they received a triggering provocation augmented aggression toward the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
4
21
2
1
Order By: Relevance
“…This replicates the finding by Vasquez (2009) that in the absence of inhibitory information, cognitive load produces a slight, but non-significant increase in the displacement of aggression. As predicted, presenting an inhibitory cue (that others would learn about the participants' aggressive reaction) decreased TDA toward the triggering individual, but only when participants were under low cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This replicates the finding by Vasquez (2009) that in the absence of inhibitory information, cognitive load produces a slight, but non-significant increase in the displacement of aggression. As predicted, presenting an inhibitory cue (that others would learn about the participants' aggressive reaction) decreased TDA toward the triggering individual, but only when participants were under low cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
“…As a result, cognitive load can change the perceptions of, and reactions to, social situations and events (Forgas, 1995). Vasquez (2009), for instance, found that cognitive load increases TDA when the trigger was high in salience. Situations in which individuals become motivated to aggress are examples of such contexts.…”
Section: Cognitive Load and Tdamentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, people who experience conflict are likely to feel distressed and their self-esteem may be threatened (Dijkstra, Van Dierendonck, & Evers, 2005;Frone, 2000;Giebels & Janssen, 2005; see also Vasquez, 2009). Furthermore, conflict induces rigidity of thinking and increases people's cognitive load, which diminishes their capacity to perform (Carnevale & Probst, 1998 We expect similar processes to operate in the case of bystander conflict, thereby negatively influencing the performance of the task at hand.…”
Section: Bystander Conflict and Performancementioning
confidence: 91%